Investing in non-communicable disease risk factor control among adolescents worldwide: a modelling study - David Watkins; Jessica Hale; Brian Hutchinson; Ishu Kataria; Vasilis Kontis; Rachel Nugent (BMJ Global Health)
Introduction Exposure to non-communicable disease (NCD) risk factors is increasing among adolescents in most countries due to demographic, economic and epidemiological forces. We sought to analyse the potential health impact and costs of implementing NCD risk reduction interventions among adolescents worldwide.Methods We identified six interventions targeted at adolescent tobacco smoking, heavy episodic drinking and obesity and supported by effectiveness and cost-effectiveness evidence. Based on a population-level cohort of adolescents in 70 representative countries, we assessed the global mortality consequences of fully implementing these interventions over 2020–2070 using the potential impact fraction approach. We calculated the economic benefits of reduced mortality and estimated the required financial costs, discounting both at 3% annually. We also conducted best-case and worst-case scenario analyses.Results Full implementation of these interventions worldwide could avert nearly 10% of premature deaths among this cohort, translating to about US$400 billion in cumulative economic benefits. Cumulatively, the required costs would be about US$85 billion, suggesting that every US$1 of public money invested would generate US$5 in increased human capital. Tobacco taxes generally conferred the highest economic returns; however, an in-depth analysis of three countries illustrated the potential for different priorities, such as alcohol control, to emerge.Conclusion From a life course perspective, implementation of a package of interventions to reduce NCD risk among adolescents worldwide would substantially reduce premature mortality at reasonable costs. Our analysis illustrates the importance of integrating NCD prevention policies into the emerging global agenda for adolescent health and well-being.